2020
DOI: 10.3310/hta24300
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic removal of impacted mandibular third molars: a systematic review and economic evaluation

Abstract: Background Impacted third molars are third molars that are blocked, by soft tissue or bone, from fully erupting through the gum. This can cause pain and disease. The treatment options for people with impacted third molars are removal or retention with standard care. If there are pathological changes, the current National Institute for Health and Care Excellence guidance states that the impacted third molar should be rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 144 publications
3
22
0
Order By: Relevance
“…The findings of the present study did not confirm this eventual statement, although pain was strongly associated with this condition (trismus), especially until the fifth postoperative day (day 5). Trismus has been associated with extractions of 3Ms, as well as, surgical time and complexity of the procedure and also with development of infection and dry socket (22,23). The current study corroborates the findings in the literature regarding association between trismus and the length of the procedure, as well as, observes that the operator's perception of the surgery complexity is also associated with a greater reduction in mouth opening.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present study did not confirm this eventual statement, although pain was strongly associated with this condition (trismus), especially until the fifth postoperative day (day 5). Trismus has been associated with extractions of 3Ms, as well as, surgical time and complexity of the procedure and also with development of infection and dry socket (22,23). The current study corroborates the findings in the literature regarding association between trismus and the length of the procedure, as well as, observes that the operator's perception of the surgery complexity is also associated with a greater reduction in mouth opening.…”
Section: Discussionsupporting
confidence: 89%
“…Third molar extraction is one of the most common invasive procedures in dentistry (21) and, in these procedures, patients may experience discomfort, restriction in daily activities and, in addition, patients may experience postoperative complications such as pain and trismus, among others (22,23). In this observational and prospective clinical trial, it was sought to know the effect and interaction produced by dental anxiety in postoperative pain and trismus following 3Ms extractions with different degrees of difficulty and extension, giving to this study a clear differential, since standardization with similar procedures has been the rule in this type evaluation in the current literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies elucidate reasons to indicate 3M removal, such as caries, periodontitis, and pain 1 , 2 , 5 , 16 , 17 . A current systematic review concluded that the evidence comparing the prophylactic removal of impacted lower 3M with its retention is very limited 18 . Although sufficient evidence is lacking, the authors suggest that prophylactic removal may be the most cost-effective strategy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A current systematic review concluded that the evidence comparing the prophylactic removal of impacted lower 3M with its retention is very limited 18 . Although sufficient evidence is lacking, the authors suggest that prophylactic removal may be the most cost-effective strategy 18 . However, these results are related to impacted teeth and systematic reviews evaluating the effectiveness of removing partially erupted teeth were not found.…”
Section: Discussionmentioning
confidence: 99%
“…The subcutaneous emphysema possibly developed when the right mandibular, semi-impacted, horizontally placed third molar was extracted after sectioning using an air-turbine handpiece 2 days before CT imaging; the extraction was performed before C-ion RT to ease oral care following irradiation to the head and neck region, as food impaction was likely to occur under the mucosa overlying the semi-impacted tooth. 1 The blue arrow indicates the socket from which the third molar was extracted ( Figure 2 ). In this case, it is probable that when the mucoperiosteal flap formed and the third molar was sectioned with an air-turbine handpiece, air invaded the soft tissues from the mucoperiosteal flap 2 and spread to the parapharyngeal space ( Figure 4 ).…”
mentioning
confidence: 99%